Management of Young Professionals Success in the Labor Market - Natalia A. Orekhovskaya; Sergei Y. Lavrentiev; Elmira R. Khairullina; Olga G. Yevgrafova; Zavgaria M. Sakhipova; Irina V. Strakhova; Natalya V. Khlebnikova; Marina N. Vishnevskaya (International Review of Management and Marketing, 2016)
The relevance of the study is determined by the new socio-cultural situation caused by the development of the information society. The purpose of the article is to identify the relationship between the general cultural competence and professional success of young professionals. The main idea of research is the theory of vocational education's humanization. The data is given of the author's sociological survey on the definition of the general cultural level of the students. The authors have developed the principles of management of young professional's success in the labor market from the perspective of humanization of education. The authors have shown the need to increase the level of common cultural competence among the majority of modern college students, providing a successful self-realization in the labor market. Article Submissions may be useful for developers of the federal state educational standards at all levels of education, teachers and heads of vocational educational institutions and professional higher education institutions, sociologists dealing with youth employment and education.